“If I was to post something, it would be too vulnerable:” University students and mental health disclosures on instagram - Budenz, Alexandra; Klassen, Ann; Purtle, Jonathan; Yudell, Michael; Massey, Philip (Journal of American College Health, 2020)
Objective: Assess Instagram use for mental health disclosure in university students to assess the potential for Instagram use as mental health support-seeking. Participants: Twenty-one students using mental health services while attending a private, Mid-Atlantic university between 6/2017-12/2017. Methods: Collected qualitative interview and Instagram data and analyzed them in parallel. Instagram data supplemented interview themes and were coded and analyzed quantitatively to define features of participants’ Instagram use. Results: Participants displayed aversions to posting mental health disclosures on Instagram, citing public and self-stigma as barriers to disclosure. Despite this, participants reported instances in which their Instagram posts directly or indirectly reflected their lived experiences. Some also maintained second anonymous accounts for fuller disclosure. Conclusions: Given the benefits of mental health disclosures to well-being and the predilection for social media use in university students, student and university-led initiatives to promote social media environments conducive to disclosures could have widespread mental health benefits.